2017
DOI: 10.20961/hpe.v5i2.18298
|View full text |Cite
|
Sign up to set email alerts
|

IMPLEMENTASI KEBIJAKAN PENCEGAHAN dAN PENANGGULANGAN HUMAN IMMUNODEFICIENCY/AQUIRED IMMUNE DEFICIENCY SYNDROME (HIV/AIdS) dI KOTA SURAKARTA

Abstract: Abstract<br />This Articel to analyze the implementation of policy on the prevention and combat of Human Immunodefisiency Virus and Aquired Immune Deficiency Syndrome (HIV/AIDS) in Surakarta City. This type of research in writing this is a non-doctrinal/empirical, with basing on the concept of the law of the 5th. The form used is the research diagnostic analysis. The data type of the data source, and the primair include primary and secondary legal materials. Data analysis using qualitative analysis. Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
1
0
2
Order By: Relevance
“…This is in line with Edward III's thesis that effective communication determines how well policies are implemented [12]. This is in line with Wahyuningsih's research (2017), which demonstrates that the lack of program policy socialization, as well as the incomplete dissemination and accessibility of information about health services and the lack of VCT services, are some of the factors that have prevented HIV/AIDS prevention from being maximized [11]. This is consistent with the findings of Setiyawati's (2014) study, which found that housewives of all demographics favor HIV/AIDS testing.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…This is in line with Edward III's thesis that effective communication determines how well policies are implemented [12]. This is in line with Wahyuningsih's research (2017), which demonstrates that the lack of program policy socialization, as well as the incomplete dissemination and accessibility of information about health services and the lack of VCT services, are some of the factors that have prevented HIV/AIDS prevention from being maximized [11]. This is consistent with the findings of Setiyawati's (2014) study, which found that housewives of all demographics favor HIV/AIDS testing.…”
supporting
confidence: 81%
“…The successful execution of the program will depend on everyone's understanding of the policy's provisions. The fact that the issue was not prioritized by the health sector or the connected development sector and that the program received insufficient political backing, was one of the reasons why HIV prevention efforts were not optimized [11].…”
mentioning
confidence: 99%
“…Prevalensi HIV tertinggi terjadi pada kelompok usia 25-49 tahun (70,7%) dengan persentase kasus HIV lebih tinggi pada laki-laki (62%) daripada perempuan (38%). Transmisi HIV terjadi melalui berbagai cara, seperti hubungan heteroseksual, hubungan homoseksual, dan penggunaan jarum suntik yang bergantian[1]- [4] HIV/AIDS (Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome) merupakan salah satu permasalahan kesehatan global yang serius. Penyakit ini telah menyebabkan jutaan kematian dan dampak negatif yang signifikan terhadap kualitas hidup individu yang terinfeksi.…”
Section: Latar Belakangunclassified
“…36 Tahun 1994 tentang Komisi Penanggulangan AIDS yang diperbarui melalui Peraturan Presiden No. 75 Tahun 2006 tentang Komisi Penanggulangan AIDS Nasional (Wahyuningsih, Novianto, & Purwadi, 2017).…”
unclassified